KEMAMPUAN MENULIS CERPEN SISWA KELAS X SMA SEMEN PADANG DENGAN MENGGUNAKAN TEKNIK PEMODELAN - Sari, Desi Melia; Eska, Wirnita; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2013)
Background of this research is how the ability to write short stories grade 10 Semen Padang senior high school students using modeling techniques. The problem posed by the following research question : how the ability to write short stories grade 10 Semen Padang senior high school studentsÂ in terms of characterizations , events and background on stories . This research aims to determine the ability to write short stories grade 10 Semen Padang senior high school students using modeling techniques. This type of research is descriptive quantitative method. I have chosen research sites in Semen Padang senior high school. Data were collected by using the performance tests in writing short stories. Outcomes studied were rated based formula has been set and the results in total.Â Analyzed using five levels, namely excellent, good, enough, less, and less so. As for the informants in this study consists of the principal , vice-principal , a part of the curriculum , 3 teachersÂ of Indonesian, and 34 people of all grade 10 Semen Padang senior high school students, through a modeling technique like RPP, observation and interview . Data were tested using student test performance, the data were analyzed with the modeling technique consists of collecting data and drawing conclusions. Based on the results of data analysis showed that the ability to write short stories grade 10 Semen Padang high school students by using modeling techniques in terms of characterizations, events, and background are on average 70% in the range of 66-755. The conclusion that can be drawn in this research is that the ability to write short stories grade 10 Semen Padang high school students by using the modeling techniques are more than enough qualifications. From the conclusions obtained, it is suggested that the teacher Indonesian and Indonesian Literature in Semen Padang senior high school to further enhance the students ability to write a short story with emphasis on providing training.